Участь педагога, психолога та лікаря у кримінальному провадженні щодо неповнолітніх - Романюк, В. В.; Romaniuk, V. V.; Віталій Романюк (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 101-109, 2014)
Уточнено коло фахівців, які можуть бути залучені до процесуальних дій під час кримінального провадження щодо неповнолітніх. Підтверджено доцільність обов’язкового залучення психолога не тільки під час проведення допиту, але й інших слідчих (розшукових) дій за участю неповнолітнього. Зазначено, що участь педагога, психолога та лікаря як спеціалістів є засобом включення до кримінального провадження щодо неповнолітніх неюридичних знань, що забезпечує індивідуальний підхід до неповнолітніх, притаманний для ювенальної юстиції.

The relevance of the research concerning participation in the criminal proceedings against minors such specialists as a teacher, psychologist and physician is due to the creation of the juvenile justice system in Ukraine. It is noted that the main issues related to the participation of teachers, psychologists and physicians concern the forms of using their expertise, the nature of involving these persons (mandatory or optional), and adjusting the range of professionals, who may be involved in criminal proceedings against minors. The range of persons, who may be involved in the criminal proceedings against minors such as a teacher, psychologist or physician, is specified. It is noted that the participation of these professionals is a mean of inclusion of non-legal knowledge in the criminal proceedings against minors as a special type of procedural activity, providing individual approach to minors. It is stressed that a teacher or psychologist as specialists must assist an investigator, prosecutor, court to clarify the circumstances of the case, without their legal assessment. The feasibility of mandatory involvement of a psychologist in criminal proceedings against minors in terms of getting close consultation conclusion as to the identity of a minor is confirmed. The necessity of legislative proposals that involve the participation of a specialist-psychologist during either questioning or other investigative (search) actions involving minors is stated. It is concluded that participation of a teacher, psychologist, physician in criminal proceedings against minors regarding the use of their expertise will improve the efficiency of the proceedings in general and concentrating attention on the interests of a minor.

Уточнен круг специалистов, которые могут быть привлечены к уча- стию в процессуальных действиях в ходе уголовного производства в отношении несовершеннолетних. Подтверждена целесообразность обязательного привлечения психолога не только во время проведения допроса, но и других следственных (розыскных) действий с участием несовершеннолетнего. Указано, что участие педагога, психолога и врача как специалистов является средством включения в уголовное производство в отношении несовершеннолетних неюридических знаний, что обеспечивает индивидуальный подход к несовершеннолетним, присущий для ювенальной юстиции.
Participation of a teacher, psychologist and physician in the criminal proceedings against minors
Участие педагога, психолога и врача в уголовном судопроизводстве в отношении несовершеннолетних
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; несовершеннолетние; использование специальных знаний; уголовное судопроизводство; ювенальная юстиция; педагог; teacher; психолог; лікар; doctor; врач; psychologist; minors; institution of expertise application; juvenile justice; уголовное производство; кримінальне провадження; неповнолітні; інститут застосування спеціальних знань; використання спеціальних знань; кримінальне судочинство; ювенальна юстиція; спеціальні знання; специальные знания